Modelling Of An Educational Gas Turbine System And Controller Design Using LMS Algorithm - Aidil Azwin Bin Zainul Abidin (2023)
Gas turbines are used extensively in generation due to the ability to pick up load faster than any other thermal methods. For this reason a control method for it is very